FEATURES OF THE USE OF COLLABORATIVE INDUSTRIAL ROBOTS AND PROSPECTS FOR THE DEVELOPMENT OF COLLABORATIVE TECHNOLOGIES - PYLYPENKO, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Industrial robots (IRs) are an important component of modern industrial production, where they perform various technological operations that are complex and/or dangerous for humans. Technological advancements and Industry 4.0 trends have led to the proliferation of special types of robots, among which collaborative industrial robots (CIRs) have found wide application in production. The peculiarity of the latter is the ability to interact with people and perform technological operations together. CRCs have a number of features and advantages compared to "classical" PRs, for example, the ability to program the movements of the robot's manipulation system with the help of external human manual action, the so-called hand guiding. The functional, hardware, and software capabilities of CRC features, including sensors and security systems that allow robots to perceive the environment and interact with people, are considered. The most common methods of perceiving changes in the CRC environment are the use of optical sensors, electromagnetic sensors, mechanical sensors, modern technologies of technical vision and artificial intelligence. The types of interaction between humans and CRCs are highlighted, which are divided into: coexistence, synchronization, cooperation and collaboration. This paper focuses on the prospects for the development of CRCs in modern industrial production. The analysis of available information sources on the peculiarities of application and research of PR and CRC is carried out, which indicated the relevance and prospects of the areas of collaborative and cognitive robotics. The prospects for the use of CRC in various fields, including non-productive industries, and the further evolution of CRC to cognitive robotics, which involves providing robots with intellectual functions and wide decision-making capabilities, including during the technological process, are highlighted. The importance of CRC as a transitional stage to cognitive robotics is emphasized.
Keywords: industrial robot; collaborative robotics; cognitive robotics; automation; safety